Growth analysis of Mombaça grass in silvopastoral and monoculture systems managed under different canopy heights - Rodrigues, Marcos Odilon Dias; Rodrigues, Marcio Odilon Dias; Silveira Júnior, Otacílio; Lima, Ítalo Cordeiro Silva; Santos, Antonio Clementino dos (Revista de Ciências Agroveterinárias, 2024)
The purpose of this study was to evaluate growth characteristics of Mombaça grass in silvopastoral and monoculture systems under different canopy heights. Monoculture and silvopastoral systems were evaluated under different height management strategies which were: 70, 80, 90 and 100 cm, in two seasons of the year: rainy and rainy / dry transition seasons. The variables evaluated were LAR (Leaf area ratio), SLA (Specific Leaf Area), LWR (Leaf Weight Ratio), RGR (Relative Growth Rate), CGR (Crop Growth Rate), NAR (Net Assimilation Rate) and LAI (Leaf Area Index). The experimental design adopted was randomized blocks with five replications. Data were subjected to analysis of variance and F test, and the Duncan test was used to compare the systems. The effect of the cutting height was assessed through linear and quadratic regression equations (p> 0.05). The shade cast by the trees affects most of the growth characteristics of Mombaça grass, such as SLA and LWR, which increased to compensate for the lower light intensity reaching the understory. Growth characteristics linked to the efficiency of light assimilation tend to be greater in the silvopastoral system. Characteristics related to production such as CGR and LAI were superior in the monoculture system. The strategy of cutting the forage at a height of 70 cm with residue of 40 cm showed the best growth rates in comparison to the other cutting strategies in the silvopastoral system.